Assessments of Prevalence of Ponticulus Posticus, Atlas Posterior Arch Deficiency, Sella Turcica Bridging, Maxillary Canine Impaction, and Associations Among Them in 500 CBCTs of Italian Orthodontic Patients - Macrì, Monica; Perrella, Giada; Varvara, Giuseppe; Murmura, Giovanna; Traini, Tonino; Rendina, Fabiola; Festa, Felice (Frontiers in Dental Medicine, 2021)
Background: The ponticulus posticus (PP) is an important anomaly of the atlas (C1 vertebra) with a complete or partial bone bridge that transforms the groove of the vertebral artery (VA) into a canal (arcuate foramen). The aim was to retrospectively determine prevalence of PP evaluating morphological features and the possible association with other dentoskeletal anomalies in the midface and neck area such as maxillary canine impaction (MCI), atlas posterior arch deficiency (APAD), and sella turcica bridging (SB). Methods: This study was conducted in the Department of Medical, Oral and Biotechnological Sciences of the University “G. D'Annunzio” in Chieti. The detection of PP was performed on 500 patients with cone beam CT (CBCT) images (6 to 87 years). Results: Analysis revealed the presence of uni- and bi-lateral PP in 110 patients (22%): 24 (4.8%) patients with bilateral complete PP, 12 (2.4%) patients with complete PP on the left, 6 (1.2%) patients with complete PP on the right, 8 (1.6%) patients with complete PP on the right and partial PP on the left, 6 (1.2%) patients with complete PP on the left and partial PP on the right, 26 (5.2%) patients with partial bilateral PP, 18 (3.6%) patients with partial left PP, and 10 (2%) patients with partial PP on the right. The Chi-squared statistic confirmed that there are significant associations between MCI and PP (p = 0.020) and between SB and MCI (p <0.00001). No correlation between chronological age and presence of the PP (p = 0.982), between chronological age and morphotypes of the PP (p = 0.779), between APAD and the PP (p = 0.0757), between SB and the PP (p = 0.111), and between APAD and MCI (p = 0.222) were found. Conclusion: This observational study showed how bilateral partial variant and bilateral complete variant are the most represented morphotypes in all the age groups. The prevalence of MCI is positively associated with PP and with SB.